Keanekaragaman Komunitas Artropoda Predator Tanaman Padi yang Aplikasi Boinsektisida Berbasis Jamur Entomopatogen Daerah Rawa Lebak Sumatera Selatan - khodijah khodijah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Species diversity and abundance of canopy-inhabiting and soil-dwelling arthropods  could be affected by pesticide application. Population and the intensity of the rice stem borer attack can influence pesticide application. This study aimed to examine  the effect of the application of solid  and liquid bio insecticide entomopathogenic fungus Beauveria bassiana-based  formulations on species diversity and abundance of predatory arthropods  in inhabiting paddy canopy  and soil dwelling. The research was conducted in fresh-water swamp  rice cultivation in Pelabuhan Dalam village,  Pemulutan district,  Ogan Ilir regency in South Sumatra, from Mei to Agustus 2012.  The results showed that the application of liquid and solid bioinsecticida affected predatory arthropods diversity (H') at rice plant canopy.  The highest effect was found in rice plant applied with liquid bio insecticide and the lowest effect with synthetic insecticides.  Predatory arthropods diversity (H') in soil dwelling   was the highest in rice plants applied with solid bioinsecticide and the lowest with synthetic insecticides